Analisis Perilaku Masyarakat Dalam Penggunaan Jamban - Erna Erna; Andi Yusuf; Rahmawati Azis (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: Government efforts have been made to improve environmental sanitation in support of national commitments and the achievement of the target of the SDG's agreement related to sanitation, namely increasing access to clean water and basic sanitation on an ongoing basis. Problems with proper sanitation include the high number of people not using latrines that meet health standards. Objective: to know the behavior of the community in using healthy latrines. Methods: The research used was observational (quantitative) with a cross-sectional study design. Results: showed that the level of knowledge did not have a significant relationship with the use of latrines (p=0,273>α0.05, the level of income had a significant relationship with the use of latrines =0.000<α=0.05, the condition of the latrines had a significant relationship with the use of latrines = 0.000<α=0.05 and the support of community leaders were significantly related to the use of latrines = 0.000<α=0.05. While the condition of the latrine is the variable that most influences the use of the latrine, with a significant value (sig. = 0.000) or p-value < 0.000 and the value of Exp (B) = 39,030. Conclusion: income and support from community leaders related to latrine use. The most influential factor on the use of latrines is the condition of the latrine. It is hoped that the support of community leaders will motivate and support the community to always maintain sanitation in their environment. The government in addition to providing education to the community also facilitates the construction of latrines equipped with the provision of clean water